Ionic liquid-mediated microstructure regulations of layered perovskite for enhanced visible light photocatalytic activity - Hailili, Reshalaiti; Bahnemann, Detlef W.; Schneider, Jenny (Frontiers in Catalysis, 2022)
The presence of pollutants e.g., pharmaceutical residues and industrial pollutants causes serious risks and irreversible damage to public health and ecological balance. Semiconductor-based photocatalysis is an attractive way to treat polluted water. Rational design and nanostructuring of semiconductors with visible light absorption and prominent surfaces could strengthen surface-interface reactions, resulting in improved photocatalytic degradation. Herein, layered structured perovskites Bi4Ti3O12 (BTO) were synthesized by an ionic liquid (1-butyl-3-methylimidazolium iodide, [Bmim]I) assisted approach. The precise tuning of synthetic conditions allowed formations of various microstructures, including spherical nanoparticles, nanoplates and nanorods, respectively. The optical analyses demonstrated that samples were typically visible light absorbents with narrow band gap energies (2.96 eV 2.73 eV), and displayed pronounced degradation for pharmaceutical residues under visible light illumination. The factors responsible for the high efficiency of BTO photocatalysts were discussed in terms of unique structure, optical alignment, dipole induced carrier separation and formation of active radicals. Among studied samples, the nanorod shaped BTO showed 1.31 and 1.46 times higher apparent rate constants for tetracycline and ibuprofen degradation than its counterparts (spherical nanoparticles and nanoplates), respectively. The better performance of nanorods was ascribed to their higher visible light harvesting ability. Importantly, BTO nanorods exhibited nonselective degradation activity for diverse pollutants of pharmaceutical residues and industrial contaminants. This work demonstrates the unique strategy of microstructure regulation and a wide range of applications of layered perovskites for environmental remediation.